Decreased Risk of Influenza in Child and Adolescent Patients with Attention-Deficit Hyperactivity Disorder Following Methylphenidate Treatment: A Nationwide Cohort Study in Taiwan - Lee H; Chen VCH; Yang YH; Kuo TY; Lin TC; Wu SI; Kao KL; Weng JC; Kelsen BA; Liang SHY (Neuropsychiatric Disease and Treatment, 2020)
Hsuan Lee,1,* Vincent Chin-Hung Chen,2,3,* Yao-Hsu Yang,4– 6 Ting-Yu Kuo,4 Tzu-Chin Lin,7,8 Shu-I Wu,9,10 Kai-Liang Kao,11,12 Jun-Cheng Weng,3,13 Brent Allan Kelsen,14,15 Sophie Hsin-Yi Liang2,16 1Department of Psychiatry, Taipei Veterans General Hospital, Taipei, Taiwan; 2Department of Medicine, Chang Gung University, Taoyuan, Taiwan; 3Department of Psychiatry, Chang Gung Memorial Hospital at Chiayi,Chiayi,Taiwan; 4Health Information and Epidemiology Laboratory of Chang Gung Memorial Hospital, Chiayi Branch, Chiayi,Taiwan; 5Department of Traditional Chinese Medicine, Chang Gung Memorial Hospital,Taiwan; 6School of Traditional Chinese Medicine, College of Medicine, Chang Gung University, Taoyuan, Taiwan; 7Bethel Psychiatric Clinic, Taipei, Taiwan; 8Institute of Science, Technology and Society, National Yang-Ming University Taipei, Taiwan; 9Mackay Memorial Hospital, Section of Psychiatry, Taipei, Taiwan; 10Department of Medicine, Mackay Medical College, Taipei, Taiwan; 11Department of Pediatrics, Far Eastern Memorial Hospital, Taipei, Taiwan; 12Department of Industrial Management, Oriental Institute of Technology, Taipei, Taiwan; 13Department of Medical Imaging and Radiological Sciences, Chang Gung University, Taoyuan, Taiwan; 14Language Center, National Taipei University, New Taipei City, Taiwan; 15Department of Psychology, Auckland University of Technology, Auckland, New Zealand; 16Department of Child Psychiatry, Chang Gung Memorial Hospital at Taoyuan, Taoyuan, Taiwan*These authors contributed equally to this workCorrespondence: Sophie Hsin-Yi LiangDepartment of Child Psychiatry, Chang Gung Memorial Hospital at Taoyuan, No. 123, Dinghu Road, Guishan Township, Taoyuan 333, TaiwanEmail sophie.lhy@gmail.comBackground: Young individuals with attention-deficit hyperactivity disorder (ADHD) may have an elevated risk of influenza because of the difficulty in complying with the behavioral procedures that help protect against influenza. Moreover, the effects of sufficient methylphenidate treatment on influenza have received little attention.Objective: This study evaluated the association between ADHD medication usage and influenza and assessed the effect of duration of ADHD treatment on the risk of influenza using a nationwide population-based database.Methods: This study investigated methylphenidate usage and the risk of influenza among children and adolescents with ADHD. We identified 5259 young individuals aged less than 18 years who were diagnosed as having ADHD between 1996 and 2013 from the National Health Insurance Research Database of Taiwan, and we tested whether methylphenidate use affects influenza risk using Cox proportional hazard models.Results: After controlling for confounding factors, the results indicated that influenza risk significantly reduced in the group of ADHD patients who were prescribed methylphenidate for 90 days and more (hazard ratio [HR]: 0.62, 95% confidence interval [CI]: 0.52– 0.75, p< 0.001), demonstrating a 38% reduction in the risk of influenza in this group. However, this was not observed in the group of ADHD patients who used methylphenidate for 1– 90 days (HR: 0.69, 95% CI: 0.89– 1.05, p=0.12).Conclusion: The lower incidence of influenza observed in the group prescribed with methylphenidate for a longer period highlights the importance of compliance to medication and psychoeducation with regard to ADHD management.Keywords: ADHD, influenza, methylphenidate